URGENSI REGULASI PENYELESAIAN KONFLIK UMAT BERAGAMA: PERSPEKTIF TOKOH LINTAS AGAMA - Abu Hapsin (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2014)
This study aims to determine the attitudes and views of interfaith leaders with the existence of regulations related to issues of religious harmony in Indonesia, whether these regulations have significant benefits for efforts to resolve religious conflicts in Indonesia or vice versa. This research was conducted in Central Java using a qualitative approach. The data was taken from the ideas of interfaith leaders in Semarang and various related references. Data collection was taken by interview and literature study. The data were analyzed descriptively critically. The results of the study indicate that religious conflicts that occur due to various factors or the root causes of conflicts are very diverse. Each religious figure has a different view. Some people consider pluralism as the root cause of conflict, there are also opinions that the cause of conflict is discrimination in the formulation of regulated laws and regulations. Although their views differ on the root causes of the conflict, they agree that in order to maintain religious harmony in Indonesia, there needs to be a law that regulates the rules of religious life in Indonesia.